2019
DOI: 10.1128/aac.01154-19
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Minocycline against U.S. Isolates of Acinetobacter baumannii-Acinetobacter calcoaceticus Species Complex, Stenotrophomonas maltophilia, and Burkholderia cepacia Complex: Results from the SENTRY Antimicrobial Surveillance Program, 2014 to 2018

Abstract: We evaluated the activity of minocycline and comparator agents against a large number of Stenotrophomonas maltophilia (n = 1,289), Acinetobacter baumannii-Acinetobacter calcoaceticus species complex (n = 1,081), and Burkholderia cepacia complex (n = 101) isolates collected from 2014 to 2018 from 87 U.S. medical centers spanning all 9 census divisions. The isolates were collected primarily from hospitalized patients with pneumonia (1,632 isolates; 66.0% overall), skin and skin structure infections (354 isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 24 publications
3
45
0
Order By: Relevance
“…Among the tetracyclines, minocycline was as active as or more active than tigecycline, eravacycline, and omadacycline and demonstrated the highest susceptibility (78.6%) against the most difficult-to-treat group of isolates nonsusceptible to both levofloxacin and TMP-SMZ. These results are consistent with those of a recent study by Flamm et al, who reported that 64/69 (92.8%) TMP-SMZ-resistant S. maltophilia isolates (including 54/69 levofloxacin-NS isolates) were susceptible to minocycline (20). While rare in the clinical setting, we did identify three S. maltophilia isolates nonsusceptible to levofloxacin, minocycline, and TMP-SMZ, and no agent tested in this study was active against all three of these isolates.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Among the tetracyclines, minocycline was as active as or more active than tigecycline, eravacycline, and omadacycline and demonstrated the highest susceptibility (78.6%) against the most difficult-to-treat group of isolates nonsusceptible to both levofloxacin and TMP-SMZ. These results are consistent with those of a recent study by Flamm et al, who reported that 64/69 (92.8%) TMP-SMZ-resistant S. maltophilia isolates (including 54/69 levofloxacin-NS isolates) were susceptible to minocycline (20). While rare in the clinical setting, we did identify three S. maltophilia isolates nonsusceptible to levofloxacin, minocycline, and TMP-SMZ, and no agent tested in this study was active against all three of these isolates.…”
Section: Discussionsupporting
confidence: 93%
“…Bacterial isolates were specifically chosen by their phenotypic resistance to first-line agents to elucidate potential alternative treatment options, although this obviously enriched the sample with isolates outside the normal MIC distribution, which may not accurately reflect the activity of the antimicrobial agents tested in routine clinical practice (17,38). A recent evaluation of 1,289 isolates of S. maltophilia (20). Additional limitations include the number of isolates, lack of molecular analysis of all isolates, and exclusion of pipeline agents that may have activity against MDR S. maltophilia (e.g., cefiderocol and aztreonam-avibactam).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the adverse effect-profile of these drugs and the low serum concentrations achieved by tigecycline should also be taken into consideration [45]. Besides this, concerns have been raised that the frequent use of minocycline for the therapy of Acinetobacter calcoaceticus-baumannii complex may lead to the emergence of resistance in S. maltophilia [46].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of disease caused by A. baumannii strains have recently been reviewed by Morris et al [ 8 ]. The latest review on the resistance mechanisms of A. baumannii [ 542 ] focuses on XDR resistance.…”
Section: Clonally Evolving Pan-genomic Eskape Pathogensmentioning
confidence: 99%